1998
DOI: 10.1161/01.res.82.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Dofetilide Block of HERG K + Channels

Abstract: The human ether-a-go-go-related gene (HERG) encodes a K+ channel with biophysical properties nearly identical to the rapid component of the cardiac delayed rectifier K+ current (IKr). HERG/IKr channels are a prime target for the pharmacological management of arrhythmias and are selectively blocked by class III antiarrhythmic methanesulfonanilide drugs, such as dofetilide, E4031, and MK-499, at submicromolar concentrations. By contrast, the closely related bovine ether-a-go-go channel (BEAG) is 100-fold less se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
314
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(351 citation statements)
references
References 32 publications
34
314
2
1
Order By: Relevance
“…2e). This finding was unexpected because previous studies concluded HERG channel inactivation was required for high-affinity drug block (11,12), suggesting that enhanced inactivation might increase drug potency.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…2e). This finding was unexpected because previous studies concluded HERG channel inactivation was required for high-affinity drug block (11,12), suggesting that enhanced inactivation might increase drug potency.…”
Section: Resultsmentioning
confidence: 76%
“…However, the eag channel is relatively insensitive to block by dofetilide (11) and MK-499 (IC 50 Ͼ 10 M; data not shown). Unlike HERG, eag channels do not inactivate.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been reported that the removal of the rapid inactivation, which has been labeled as C-type inactivation, 17 resulted in the reduction of the sensitivity of hERG channels to E-4031 and dofetilide. 18,19 Mitcheson et al 20 showed that hERG mutations that shifted the inactivation curve toward either negative or positive directions resulted in the loss of sensitivity to drugs. These results underline the importance of the C-type inactivation in high-affinity drug binding and also suggest the involvement of other factors.…”
Section: Discussionmentioning
confidence: 99%
“…1, compare B2, B3) and in cultured astrocytes, respectively. In addition to E4031, dofetilide has been widely used to specifically block ERG (Kiehn et al, 1996;Ficker et al, 1998) (Fig. 1 B).…”
Section: Erg Expression In Hippocampal or Cultured Astrocytesmentioning
confidence: 99%